Greening Aid? [electronic resources] : Understanding the Environmental Impact of Development Assistance / by Robert L. Hicks, Bradley C. Parks, J. Timmons Roberts, Michael J. Tierney. - Hicks, Robert L.
Includes biographical references and index.